Aluga interior: plataforma web de aluguel para ranchos e chácaras de interior - OLIVEIRA, Diego Alberti Bermejo de; PARRA, Ingrid Rodrigues; MENDES, Júlia da Silva (098, 2024)
Aluga Interior, é uma plataforma específica para o aluguel de ranchos e chácaras no interior do estado de São Paulo, que busca suprir uma carência significativa nesse mercado. Atualmente, apesar da existência de alguns sites de aluguel de propriedades, observa-se uma ausência de plataformas dedicadas exclusivamente a essa região, o que resulta na exclusão de diversos imóveis e na dispersão das informações pela internet, dificultando o processo de locação. Com o intuito de solucionar essa lacuna, o Aluga Interior foi criado utilizando linguagens HMTL, PHP, JavaScript, CSS, SQL, My SQL. Ferramentas Photoshop, Microsoft Word, Microsoft Powerpoint, Boostrap, Sublime Text, para facilitar o contato direto entre proprietários e clientes interessados, centralizando as informações em um ambiente único e acessível. A plataforma tem como propósito aprimorar a experiência de locação, oferecendo uma interface intuitiva e específica para as necessidades do público-alvo, e visa contribuir para a dinamização do mercado de aluguel de propriedades rurais no interior paulista.

The current scenario of platforms for renting out ranches and farms in the interior of the state of São Paulo is significantly lacking. Although there are websites dedicated to renting these properties, there is no specific platform for the interior, resulting in many properties being excluded from the available websites. As a result, information is scattered across the internet, making it difficult to carry out most rentals. With the aim of solving this gap, “Aluga Interior” was developed, a website entirely dedicated to renting out ranches and farms in the interior of São Paulo, with the aim of facilitating direct contact between owners and clients. Aluga Interior is a specific platform for renting ranches and farms in the interior of the state of São Paulo, which seeks to fill a significant gap in this market. Currently, despite the existence of some property rental websites, there is a lack of platforms dedicated exclusively to this region, which results in the exclusion of several properties and the dispersion of information across the internet, making the rental process more difficult. In order to solve this gap, Aluga Interior was created using HMTL, PHP, JavaScript, CSS, SQL, My SQL. Photoshop tools, Microsoft Word, Microsoft Powerpoint, Boostrap, Sublime Text, to facilitate direct contact between owners and interested clients, centralizing information in a single, accessible environment. A pl
Rent interior: web platform for renting ranches and country houses
Keywords: Aluguel; Web sites; Informação e Comunicação